Improved Emergency First Aid Knowledge Level Through Training With Algorithm-Based Accessibility Simulation Model - Sunarto Sunarto; Suryo Ediyono (Poltekkes Kemenkes Surakarta, 2022)
Background: Emergency situations can arise from various diverse conditions, can come from natural conditions, humans and technological advances that have an impact on the emergence of disasters, accidents and diseases that threaten life or cause disability. Every individual in the community needs to know the flow of accessibility in an effort to seek help and the steps to provide first aid, so it is very necessary to attend training. This can be done by participating in an algorithm-based accessibility simulation model training. Methods: This type of research is a comparative experimental study with a pretest-post test design with a control group with a cross sectional approach. The respondents involved are special lay people (members of linmas in the city of Surakarta). The sampling technique used was random sampling by spreading invitations to respondents, so that 110 respondents agreed. This research instrument was tested for expert validity, namely practitioners and academics of emergency nursing, totaling 3 people. Data were analyzed by t-test with the help of a computer Results: The results showed an increase in the value of 4.4 from the pretest (Mean = 73.5) and posttest (Mean = 77.9) and the t test results showed the value of Sig. (2-tailed) is 0.00 so it can be concluded that there is a significant difference between the pretest and posttest values. Conclusion: Training with an algorithm-based accessibility simulation model can significantly increase knowledge related to the emergency field. So it needs to be recommended to be carried out gradually, continuously and thoroughly to community members.